Effects of increasing hominy feed in diets on finishing pig performance - M L Potter; J Y Jacela; Michael D Tokach; Joel M DeRouchey; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2009)
A total of 1,035 finishing pigs (initially 79.4 lb) were used in an 84-d growth trial to evaluate the effects of increasing hominy feed on finishing pig growth performance. Pens of pigs were blocked by average initial pig BW and randomly allotted to 1 of 4 dietary treatments (10 pens per treatment) with initial weights balanced across the treatment groups. Treatments were increasing levels (0%, 12.5%, 25%, and 37.5%) of corn hominy feed added to a corn-soybean meal-based diet. All treatment diets were fed in 4 phases, and hominy feed inclusion was constant among phases. Increasing hominy feed resulted in a linear decrease (P<0.01) in ADG and ADFI from d 0 to 84. Regardless of treatment, there was no difference (P>0.35) in F/G. The lower feed consumption and poorer growth performance resulted in pigs fed diets containing any level of hominy feed weighing less than pigs fed standard corn-soybean meal-based diets at the end of the trial. These data indicate that adding corn hominy feed as an alternative ingredient in swine diets is a viable option; however, a decrease in performance should be considered when deciding if it is cost-effective to include hominy feed in finishing diets.; Swine Day, Manhattan, KS, November 19, 2009
Keywords: Swine day; 2009; Kansas Agricultural Experiment Station contribution; no. 10-014-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1020; Alternative ingredient; Hominy feed; Growth; Swine